Pendampingan Klinik Pengelolaan Barang Milik Daerah (BMD)/ Manajemen Aset - Syaikhul Fallah (UNIVERSITAS CENDERAWASIH, 2018)
The advisory activities for local property management/asset management clinic is a community service activity that has purpose in maintaining the quality of documents of regional assets are well recorded and in accordance with applicable standards and regulations. The participants of this activity are treasurer of the Department of Education and Health Services of Keerom Regency.